2018
DOI: 10.1103/physrevb.97.165417
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of the shift of the G band of double-walled carbon nanotubes due to interlayer interactions

Abstract: The interactions between the layers of double-walled carbon nanotubes induce measurable shift of the G bands relative to the isolated layers. While experimental data on this shift in free-standing double-walled carbon nanotubes has been reported in the past several years, comprehensive theoretical description of the observed shift is still lacking. The prediction of this shift is important for supporting the assignment of the measured double-walled nanotubes to particular nanotube types. Here, we report a comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 36 publications
3
25
0
1
Order By: Relevance
“…This splitting is attributed to interwall interactions within one FWCNT, where the G + mode of the inner (outer) wall shifts to a smaller (higher) frequency relative to the position in an isolated single-wall CNT. 35,45,46 This indicates that the Raman signals belong to the walls of a FWCNT, rather than to separate SWCNTs. 35,45 Overall, we imaged 14 coils by Raman spectroscopy, for 7 of which we could detect a G + mode splitting.…”
Section: Nano Lettersmentioning
confidence: 99%
“…This splitting is attributed to interwall interactions within one FWCNT, where the G + mode of the inner (outer) wall shifts to a smaller (higher) frequency relative to the position in an isolated single-wall CNT. 35,45,46 This indicates that the Raman signals belong to the walls of a FWCNT, rather than to separate SWCNTs. 35,45 Overall, we imaged 14 coils by Raman spectroscopy, for 7 of which we could detect a G + mode splitting.…”
Section: Nano Lettersmentioning
confidence: 99%
“…[42] Liu et al [19] compared the vdW interaction strength in DWCNTs with the vdW coupling between unit-area graphene sheets under pressure obtained from compressibility measurements of graphite and showed that the effective pressure between the walls of as-grown DWCNTs reaches GPa (upper scale in Figure 4a). Later, Popov et al [58] demonstrated that this effective pressure results from structural optimization of DWCNT layers, leading to radius changes (expansion/compression) as a function of both the diameter and the interlayer distance (Figure 4b). It is interesting to note that DWCNTs with Δr > 0.34 nm allow readily accessing a negative pressure on inner SWCNTs in the GPa range, which is difficult to achieve using conventional approaches.…”
Section: And the Interlayer Twist Anglementioning
confidence: 96%
“…Reproduced with permission. [58] Copyright 2018, American Physical Society. c) Raman spectrum for an individual (15,13)@(31,4) DWCNT, revealing the strong blue-shifted of DWCNT RBM frequencies from those of the constituent SWCNTs (dashed lines).…”
Section: Molecular Confinement and Alignment Inside Swcntsmentioning
confidence: 99%
See 1 more Smart Citation
“…И поскольку частота G-моды напрямую зависит от длины связи C−C, наблюдаемое явление может иметь несколько возможных объяснений. Вопервых, длина связи C−C чувствительна к изменению межслоевого расстояния в МУНТ [17,18]: чем меньше межслоевое расстояние, тем выше оказывается частота G-моды. Во-вторых, влияние на связь C−C также может оказываться посредством допирования [14,19,20] и явления переноса заряда [21], что в нашем случае может происходить за счет частиц катализатора.…”
Section: результаты и обсуждениеunclassified